Implementasi Metode K-Nearest Neighbor untuk Penentuan Lokasi Flight Information Display System - Dayu Aprellia Dwi Putri; Nurul Hidayat; Edy Santoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
The purpose of this study was to determine the location of the FIDS at Soekarno-Hatta International Airport in Jakarta using data from the FIDS equipment list. Non-implementatif analytical research methods are carried out by classifying data from the FIDS equipment list using the K-Nearest Neighbor method by dividing the data into training data and test data. The benefit of the research is to find out the results of the implementation using data from the FIDS equipment list and the results of the evaluation seen from the level of accuracy obtained so that it can determine the feasibility of using the K-Nearest Neighbor method to determine the location of FIDS. In this study it was found that the results of the implementation of the K-Nearest Neighbor method using IP Address and Terminal data as calculation data and Location data as target data can be applied properly in determining the location of FIDS because the resulting accuracy rate reaches 96,154% with the optimal K value for used in the system is 1.